Metabolite profiling of mycorrhizal roots of Medicago truncatula - Schliemann, Willibald; Ammer, Christian; Strack, Dieter (Phytochemistry (Oxford), 2008)
Extensive analyses of soluble primary and secondary metabolites as well as cell wall-bound phenolics of Medicago truncatula roots by GC–MS, HPLC, and LC–MS during the symbiotic interaction with the arbuscular mycorrhizal fungus Glomus intraradices are reported. Metabolite data sets were subjected to bioinformatics approaches including HCA, PCA and network analyses. Metabolite profiling of soluble primary and secondary metabolites, as well as cell wall-bound phenolic compounds from roots of barrel medic ( Medicago truncatula) was carried out by GC–MS, HPLC and LC–MS. These analyses revealed a number of metabolic characteristics over 56 days of symbiotic interaction with the arbuscular mycorrhizal (AM) fungus Glomus intraradices, when compared to the controls, i.e. nonmycorrhizal roots supplied with low and high amounts of phosphate. During the most active stages of overall root mycorrhization, elevated levels of certain amino acids (Glu, Asp, Asn) were observed accompanied by increases in amounts of some fatty acids (palmitic and oleic acids), indicating a mycorrhiza-specific activation of plastidial metabolism. In addition, some accumulating fungus-specific fatty acids (palmitvaccenic and vaccenic acids) were assigned that may be used as markers of fungal root colonization. Stimulation of the biosynthesis of some constitutive isoflavonoids (daidzein, ononin and malonylononin) occurred, however, only at late stages of root mycorrhization. Increase of the levels of saponins correlated AM-independently with plant growth. Only in AM roots was the accumulation of apocarotenoids (cyclohexenone and mycorradicin derivatives) observed. The structures of the unknown cyclohexenone derivatives were identified by spectroscopic methods as glucosides of blumenol C and 13-hydroxyblumenol C and their corresponding malonyl conjugates. During mycorrhization, the levels of typical cell wall-bound phenolics (e.g. 4-hydroxybenzaldehyde, vanillin, ferulic acid) did not change; however, high amounts of cell wall-bound tyrosol were exclusively detected in AM roots. Principal component analyses of nonpolar primary and secondary metabolites clearly separated AM roots from those of the controls, which was confirmed by an hierarchical cluster analysis. Circular networks of primary nonpolar metabolites showed stronger and more frequent correlations between metabolites in the mycorrhizal roots. The same trend, but to a lesser extent, was observed in nonmycorrhizal roots supplied with high amounts of phosphate. These results indicate a tighter control of primary metabolism in AM roots compared to control plants. Network correlation analyses revealed distinct clusters of amino acids and sugars/aliphatic acids with strong metabolic correlations among one another in all plants analyzed; however, mycorrhizal symbiosis reduced the cluster separation and enlarged the sugar cluster size. The amino acid clusters represent groups of metabolites with strong correlations among one another (cliques) that are differently composed in mycorrhizal and nonmycorrhizal roots. In conclusion, the present work shows for the first time that there are clear differences in development- and symbiosis-dependent primary and secondary metabolism of M. truncatula roots.